Industrial Application Of Lean Manufacturing - Wan Mahmood, Wan Hasrulnizzam; Muhamad, Mohd Razali (Universiti Teknologi MARA, 2008)
Global competition has led many manufacturing organisations to focus on productivity and quality improvement. One of the effective approaches used to achieve this is through lean manufacturing. Lean manufacturing is defined as a system based on the philosophy of waste elimination, the removal of all non-value added activities from the process of delivering a customer’s requirement in a manner that delights the customer and ensures they maintain orders. The purpose of this paper is to discuss the related issues in implementing lean manufacturing and the development strategy of improvement. The results of the study carried out on a company which had implemented lean manufacturing showed that many challenges were faced in their operation in order to establish lean manufacturing. The company has their own solution to manage the challenges while improve productivity.